Pengaruh Latihan Sepak Sila Terhadap Ketepatan Long Servis dalam Permainan Sepak Takraw Pada Siswa SMA Negeri 11 Kabupaten Buru - Asrabuana Asrabuana; Bahmid Hasbullah; Siti Divinubun (Peneliti.net, 2022)
in this study is the low ability of long serve kicks in students of SMA Negeri 11 Buru Regency. This study was to determine the effect of Silat practice on the accuracy of long serve in the game of sepak takraw on students of SMA Negeri 11 Buru Regency. This type of research is experimental. The research instrument is One Group Pretest-Posttest Desing. Total population 20 students. Existing data were tested by t-test. Based on the results of data analysis, it was obtained that tcount was 7.94 and ttable was 2.09 (tcount = 7.94 > ttable = 2.09). This means that the practice of silage affects the accuracy of long serve in the game of sepak takraw